ICARE: Development of Mathematics Student Worksheets on Sequences and Series Material - Halimah, Nur; Sari, Arnida (Suska Journal of mathematics Education, 2025)
This study aims to develop and produce learning media, using ICARE-based Student Worksheets (LKS) on sequence and series material, that meet the criteria of validity, practicality, and effectiveness. This type of research is development research with the ADDIE model. The subjects of this study were grade XI students, educational technology experts, and learning material experts. The object of the study was Learning Media using ICARE-based Student Worksheets on sequence and series material. Data collection techniques used questionnaires and test techniques. The research instruments were validation sheets for research technology experts, validation sheets for learning materials, student response questionnaires, and post-test questions. The types of data were quantitative and qualitative. The data were analyzed using both qualitative and quantitative descriptive analysis techniques. The results of this study indicate that the Learning Media, using ICARE-based Student Worksheets on Sequence and Series Material, developed, is classified as very valid and very practical for small, limited groups. The results of the effectiveness test showed that the learning media using ICARE-based Student Worksheets on sequence and series material are effective. In addition, the average value of the experimental class is higher than the average value of the control class.